Antigen-Specific TCR-T Cells for Acute Myeloid Leukemia: State of the Art and Challenges - Kang, Synat; Li, Yisheng; Qiao, Jingqiao; Meng, Xiangyu; He, Ziqian; Gao, Xuefeng; Yu, Li (Frontiers in Oncology, 2022)
The cytogenetic abnormalities and molecular mutations involved in acute myeloid leukemia (AML) make it hard to treat. Although adoptive T cell therapies (ACT) such as chimeric antigen receptors (CAR) T-cells therapy have shown promising results in leukemia treatment especially B-cell malignancies, the optimal target surface antigen has yet to be discovered for AML. Alternatively, T-cell receptor (TCR)-redirected T cells can target intracellular antigens presented by HLA molecules, allowing to explore a broader territory of new therapeutic targets of AML. For example, adoptive transfers of WT1 antigen-specific TCR-T cell immunotherapy have demonstrated positive clinical success in patients with AML. Nevertheless, AML can escape from immune system elimination by producing immunosuppressive factors or releasing several cytokine productions. This review article presents the recent advances of antigen-specific TCR-T cells in treating AML and discusses their challenges in clinical application and future exploration.